KONSEP PENDIDIKAN AKHLAK DALAM KITAB BIDAYATUL HIDAYAH KARYA IMAM AL-GHAZALI DAN RELEVANSINYA DENGAN KURIKULUM MERDEKA - Muhammad Amraldin Marpaung; Juriono Juriono; Rukmana Prasetyo (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This study aims to analyze the concept of moral education in the book Bidayatul Hidayah by Imam Al-Ghazali and examine its relevance to the implementation of the Independent Curriculum in strengthening students' character education. The research uses a qualitative approach with the type of library research and the content analysis approach. The primary data source is in the form of the book Bidayatul Hidayah by Imam Al-Ghazali, while the secondary data source is obtained from scientific articles, academic books, and official documents of the Independent Curriculum published in the 2020–2025 range. The data collection technique was carried out through documentation studies and in-depth literature review, while the data analysis used the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study show that the concept of moral education in Bidayatul Hidayah includes morality to Allah, morality towards oneself, morality towards fellow humans, and manners in the educational process. The findings of the study also show a strong relevance between the values of moral education of Imam Al-Ghazali and the dimension of the Pancasila Student Profile in the Independent Curriculum, especially in the aspects of faith, piety, noble character, independence, and social responsibility. This research contributes to strengthening the study of classical Islamic education in the context of contemporary character education and provides practical implications for the development of morality-based learning in a formal education environment.